Incidental Finding of Goblet Cell Adenocarcinoma Post Appendectomy: A Rare Case Report - Fathima Hana Mohamed Naushad; Shameema Alam; Aliya Ishaq (Dubai Medical Journal, 2025)
Introduction: One of the most frequent etiologies of an acute abdomen is appendicitis, which ranks as one of the primary reasons for surgical emergencies globally. Goblet cell adenocarcinoma (GCA) of the appendix, is hallmarked for displaying both endocrine and exocrine traits, presenting with symptoms similar to acute appendicitis, complicating its diagnosis before surgery.